2019
DOI: 10.1088/1755-1315/403/1/012162
|View full text |Cite
|
Sign up to set email alerts
|

Buckling resistance of cylinders made of textile composite material

Abstract: Composite materials were made by integration of two or more substances, one of them is a supported material like fabric, the other is a matrix material like resin. The outcome of the integration of the two substances produce new material has the attributes differ from the specifications of its constituent materials. This paper presents a comparative study of buckling resistance for cylinders made of a composite material once using a woven cloth as supporting material and the other using knitted cloth. Cylinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This is the innovation of support by the on location outside holding of a polymer tissue type compound [1,2]. This method ends up being intriguing gratitude to the high weight-opposition proportion of composite materials and their consumption obstruction, and consequently ease in execution conditions gives a fast, prudent and sturdy answer for maturing or harmed structures [3]. This innovation is spreading increasingly more in the field of structural designing.…”
Section: Introductionmentioning
confidence: 99%
“…This is the innovation of support by the on location outside holding of a polymer tissue type compound [1,2]. This method ends up being intriguing gratitude to the high weight-opposition proportion of composite materials and their consumption obstruction, and consequently ease in execution conditions gives a fast, prudent and sturdy answer for maturing or harmed structures [3]. This innovation is spreading increasingly more in the field of structural designing.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the composite materials processing industry has enjoyed rapid and steady growth, supported in particular by the diversity of applications [1][2]. Due to their properties of lightness, rigidity and specific resistance, composite materials are used today in a growing number of applications, in increasingly wide fields, ranging from aerospace research to large sporting goods public [3].…”
Section: Introductionmentioning
confidence: 99%
“…This research was conducted in a lab environment using specially designed laboratory machines and on-farm using experimental units [1].In the context of disruption of the link between a grain and an ear, it was found that multiple stress on grain mass disrupts the link between a grain and an ear. Separation of a grain and an ear rises with an increase in impact frequency, but at high speeds [3] there is a reduction [4] in the quality of a grain and excessive grain shattering [5].…”
Section: Introductionmentioning
confidence: 99%